Remote Identification of Polar Bear Maternal Den Habitat in Northern Alaska - Durner, George M.; Amstrup, Steven C.; Ambrosius, Ken J. (ARCTIC, 2001)
Polar bears (Ursus maritimus) give birth in dens of ice and snow to protect their altricial young. During the snow-free season, we visited 25 den sites located previously by radiotelemetry and characterized the den site physiognomy. Seven dens occurred in habitats with minimal relief. Eighteen dens (72%) were in coastal and river banks. These "banks" were identifiable on aerial photographs. We then searched high-resolution aerial photographs (n=3000) for habitats similar to those of the 18 dens. On aerial photos, we mapped 1782 km of bank habitats suitable for denning. Bank habitats comprised 0.18% of our study area between the Colville River and the Tamayariak River in northern Alaska. The final map, which correctly identified 88% of bank denning habitat in this region, will help minimize the potential for disruptions of maternal dens by winter petroleum exploration activities. Les ourses polaires (Ursus maritimus) donnent naissance dans des tanières de glace et de neige afin de protéger leurs petits qui sont nidicoles. Durant la saison libre de neige, on a visité 25 lieux de mise bas repérés précédemment par télémesure et on a caractérisé la structure physionomique de ces lieux. Sept tanières étaient localisées au sein d'habitats au relief très peu prononcé. Dix-huit tanières, soit 72 p. cent, se trouvaient sur des berges côtières ou fluviales. Ces «berges» étaient identifiables sur des clichés aériens. On a ensuite cherché sur des clichés aériens (n=3000) pris à haute résolution des habitats semblables à ceux des 18 tanières. Sur ces clichés, on a cartographié 1782 km d'habitats de berges appropriés à l'établissement de tanières. Les habitats de berges constituaient 0,18 p. cent de notre zone d'étude entre la rivière Colville et la Tamayariak dans l'Alaska septentrional. La carte finalisée, qui identifiait correctement 88 p. cent de l'habitat contenant des berges propres à l'établissement de tanières dans la région, aidera à minimiser le potentiel de perturbation des tanières d' ourses due aux activités de ...